New framework for the management of waqf land registration system in Malaysia - Ghazali, Nor Azimah; Sipan, Ibrahim; Mohammad, Mohammad Tahir Sabit; Ab Aziz, Muhammad Arif (Emeralds, 2021)
This paper aims to propose a new framework for the management of a waqf land registration system in Malaysia that is compliant with Islamic law and the Malaysian legal system. The study sought to answer the following two research questions: what are the issues of the waqf land registration system and how to solve the issues of waqf land registration in Malaysia.